Analyzing RFID Tags in a Distributed Environment. (2016) - Joseph, Sonia A.; Joby, N.J.
Abstract: RFID technology is widely used in various areas and found to be very useful in the business which includes supply chain management. Also the amount of RFID data is very huge as well. Hence too much time is needed to get particular information from an RFID data set. This paper proposes an efficient method to manage large amount of RFID data set. Also this proposes a unique group-id for RFID tags of unique items with which we can verify the integrity of the group of items by checking the group-id written in the tag memory. Then we devise a storage scheme called MckoiDDB that can process queries in a distributed environment. Lastly we present a graph called product localization graph to represent the tag movements in supply chain management.